Translation and activation of cultural exchanges between Kurdish and Arabic - Hamad, Pakhshan Sabir (Sulaimani Journal for Humanities, 2019)
Language can be considered as one of important means to express our insights. And the minds products and its distributions . The relationship between language and identity cannot be separated. For language is the main unit in the construction of national identity. And it is one of the challenges in front of technology. Any weakness in language leads to weakness in identity, or even the loss of national identity, and the relation between languages are very strong specially those languages with the same root in addition to the effects of religion , geographical place and trading relationship. This research that is entitled translation and motivating cultural exchange between Kurdish and Arabic, the extent of relations between these languages and the cultural exchange through exchanging words, terms, and expressions. In addition to the benefits we gain from special cultural aspect of both languages by different factors like Islamic religion and specific vocabularies attached to it. Translation factor becomes a firm bridge to pass the words and terms through them , and covering the linguistic needs and shedding lights on the vocabularies used in both languages and the transformational processes during exchanging and getting benefits from them. The approach followed by the researcher is critical analytical, which suits the nature of the research that is divided to three parts. The first part is concerned with translation and the importance of education in translation process. The second one identifies the linguistic and educational features between Kurdish and Arabic. The last one is about the estimation of the internal and external translations and the Kurdishing features .Finally the main conclusions beside abstract in Arabic and English followed by a list of references.